Isolation of new straight chain compounds from acacia nilotica - Chaubal, Rohini; Tambe, Amruta; Biswas, Sujata; Rojatkar, Supada; Deshpande, Vishnu; Deshpande, Nirinala (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2006)
A novel diester, pentacosane dioic acid dihexadecyl ester 1 has been isolated for the first time from n-hexane soxhlet extract of Acacia nilotica. Saponification of the diester reveals the presence of an alcohol, hexadecanol and pentacosane dioic acid. The structures of both the compounds are confirmed by GCMS analysis. Saponification of pet-ether extract of Acacia nilotica has been carried out. Unsaponiflable matter is further purified by column chromatography followed by repeated mixed solvent crystallization to afford heptacosan-1,2,3-triol 2.
Keywords: Acacia nilotica; diester; pentacosane dioic acid; saponification

Potential plasmid-curing agent, 8-epidiosbulbin E acetate, from dioscorea bulbifera L. against multidrug-resistant bacteria - Shriram, Varsha; Jahagirdar, Sheetal S.; Latha, C.; Kumar, Vinay; Puranik, Vedavati G.; Rojatkar, Supada; Dhakephalkar, Prashant K.; Shitole, M. G. (International Journal of Antimicrobial Agents, 2008)
Bioassay-guided fractionation of an aqueous methanolic extract of Dioscorea bulbifera L. bulbs was performed using organic solvents. A novel plasmid-curing compound was identified as 8-epidiosbulbin E acetate (EEA) (norditerpene) on the basis of modern spectroscopic analysis and X-ray crystallography. EEA exhibited broad-spectrum plasmid-curing activity against multidrug-resistant (MDR) bacteria, including vancomycin-resistant enterococci. EEA cured antibiotic resistance plasmids (R-plasmids) from clinical isolates of Enterococcus faecalis, Escherichia coli, Shigella sonnei and Pseudomonas aeruginosa with 12-48% curing efficiency. The reference plasmids of Bacillus subtilis (pUB110), E. coli (RP4), P. aeruginosa (RIP64) and Salmonella typhi (R136) were cured with efficiency ranging from 16% to 64%. EEA-mediated R-plasmid curing decreased the minimal inhibitory concentration of antibiotics against MDR bacteria, thus making antibiotic treatment more effective. The antibiotic resistance pattern revealed that the compound was effective in the reversal of bacterial resistance to various antibiotics. In addition, the compound did not show any cytotoxicity against a broad range of human cancer cell lines, namely MCF-7 (breast cancer), SiHa (cervical cancer) and A431 (epidermal carcinoma), and hence has the potential to be used as a lead compound for drug discovery programmes. (C) 2008 Elsevier B. V. and the International Society of Chemotherapy. All rights reserved.
Keywords: 8-Epidiosbulbin E acetate; Antibiotic resistance; Dioscorea bulbifera; Plasmid curing

Antibacterial & antiplasmid activities of Helicteres isora L. - Shriram, Varsha; Jahagirdar, Sheetal S.; Latha, C.; Kumar, Vinay; Dhakephalkar, Prashant K.; Rojatkar, Supada; Shitole, Mahadeo G. (Indian Journal of Medical Research, 2010)
Background & objectives: The multiple drug resistance (MDR) is a serious health problem and major challenge to the global drug discovery programmes. Most of the genetic determinants that confer resistance to antibiotics are located on R-plasmids in bacteria. The present investigation was undertaken to investigate the ability of organic extract of the fruits of Helicteres isora to cure R-plasmids from certain clinical isolates. Methods: Active fractions demonstrating antibacterial and antiplasmid activities were isolated from the acetone extracts of shade dried fruits of H. isora by bioassay guided fractionation. Minimal inhibitory concentration (MIC) of antibiotics and organic extracts was determined by agar dilution method. Plasmid curing activity of organic fractions was determined by evaluating the ability of bacterial colonies (pre treated with organic fraction for 18 h) to grow in the presence of antibiotics. The physical loss of plasmid DNA in the cured derivatives was further confirmed by agarose gel electrophoresis. Results: The active fraction did not inhibit the growth of either the clinical isolates or the strains harbouring reference plasmids even at a concentration of 400 mu g/ml. However, the same fraction could cure plasmids from Enterococcus faecalis, Escherichia coli, Bacillus cereus and E. coli (RP4) at curing efficiencies of 14, 26, 22 and 2 per cent respectively. The active fraction mediated plasmid curing resulted in the subsequent loss of antibiotic resistance encoded in the plasmids as revealed by antibiotic resistance profile of cured strains. The physical loss of plasmid was also confirmed by agarose gel electrophoresis. Interpretation & conclusions: The active fraction of acetone extract of H. isora fruits cured R-plasmids from Gram-positive and Gram-negative clinical isolates as well as reference strains. Such plasmid loss reversed the multiple antibiotic resistance in cured derivatives making them sensitive to low concentrations of antibiotics. Acetone fractions of H. isora may be a source to develop antiplasmid agents of natural origin to contain the development and spread of plasmid borne multiple antibiotic resistance.
Keywords: antibacterial activity; Antibiotic resistance; antiplasmid activity; Helicteres isora; multiple drug resistance; plasmid-curing

6 alpha-Hydroxy-4[14], 10[15]-guainadien-8 beta, 12-olide induced cell cycle arrest via modulation of EMT and Wnt/beta-catenin pathway in HER-2 positive breast cancer cells - Javir, Gitanjali; Joshi, Kalpana; Khedkar, Vijay; Rojatkar, Supada (Journal of Steroid Biochemistry and Molecular Biology, 2020)
Cyathocline purpurea has potential biological activities and has been widely used in traditional Chinese and Ayurvedic medicine. The aim of the present study is to elucidate the anticancer effect of its 6 alpha-hydroxy-4[14], 10 [15]-guainadien-8 beta, 12-olide (SRCP1) against HER-2 positive subtype of breast carcinoma. Anticancer effect of SRCP1 was assessed by cell viability, senescence, apoptosis, cell cycle, DNA synthesis, and gene expression assays. The activity was further validated by the molecular docking study. SRCP1 inhibits human HER-2 positive breast cancer growth via inhibition of DNA synthesis in a dose-dependent manner. SRCP1 induces cell cycle arrest at G(2)/M phase, late apoptosis, and necrosis. Further, it induces senescence causing reduction in migration via down-regulation of EMT. A remarkable increase in the number of necrotic cells and Annexin-V staining revealed that exposure to SRCP1 triggers late apoptosis. Treatment with SRCP1 increased E-cadherin, p21, p53, ER-alpha expression and decreased beta-catenin, MMP-9, snaill, TNF-alpha expression. SRCP1 showed binding affinity towards an active site of the HER-2 receptor. Our results of molecular docking and biological assays demonstrated the potent anticancer activity of SRCP1 in MDA-MB-453 cells via multiple pathways including EMT, TNF-alpha, and Wnt/beta-catenin signaling.
Keywords: Anticancer; beta-Catenin; EMT; Guaianolide; HER-2 inhibitor

In vitro antitubercular screening and in silico study of germacradienolide from blainvillea latifolia - Honmore, Varsha; Kalyankar, Vidya; Natu, Arun; Khedkar, Vijay; Sarkar, Dhiman; Rojatkar, Supada (Asian Journal of Chemistry, 2021)
Bioassay-guided isolation from acetone extract of Blainvillea latifolia yielded one compound. The acetone extract, fractions and the compound 1 were investigated for antitubercular activity against Mycobacterium tuberculosis H37Ra. Compound 1 showed the activity with IC50 and MIC values at 8.9 and >100 μg/mL. However, the acetone extract of Blainvillea latifolia was inactive against two Gram negative (E. coli, P. flurescence) and two Gram-positive (S. aureus, B. subtilis) bacterial strains. Hence, it was concluded that the extract and the compound 1 are specifically active against MTB and not against bacterial strains. Molecular docking study was performed against crucial mycobacterial target MtInhA to gain an insight into the binding mode and the thermodynamic interactions governing the binding affinity of this molecule.